Case report: Olverembatinib monotherapy: the chemotherapy-free regimen for an elderly patient with relapsed Ph-positive acute lymphoblastic leukemia - Ding, Jianghua; Li, Wen (Frontiers in Pharmacology, 2023)
Background: The advent of first- and second-generation BCR/ABL1 tyrosine kinase inhibitors (TKIs), such as imatinib and dasatinib, has markedly improved the clinical outcomes of patients with philadelphia chromosome–positive acute lymphoblastic leukemia (Ph+-ALL). However, due to acquired drug resistance, most Ph+-ALL patients experience relapse. Thus, third-generation BCR/ABL1 TKIs, including ponatinib and olverembatinib, have been developed with the aim of overcoming drug resistance. Case report: A 79-year-old woman presented with intermittent fever and fatigue for 4 days. After comprehensive cytogenetic examination, the patient was diagnosed with Ph+-B-ALL. Starting on 22 September 2021, a combined regimen of flumatinib and vincristine/prednisone (VP) was administered for seven cycles, followed by flumatinib maintenance therapy. The patient remained in first complete molecular remission (1st CMR) for 19 months. On 12 March 2023, she again complained of fatigue and loss of appetite for nearly a month. A comprehensive examination showed Ph+-B-ALL relapse with additional E255V mutation, although T315I mutation was negative. In view of her frail physical condition, she received olverembatinib monotherapy and achieved second CMR (second CMR). No severe toxicities were recorded except for mild fatigue. At present, she has been in second CMR for over 6 months. Conclusion: For elderly patients with relapsed Ph+-ALL, olverembatinib monotherapy may offer a novel option with a good safety profile, suggesting the feasibility of a chemo-free regimen.